2005
DOI: 10.3758/bf03193217
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of learning: Evidence for a two-stage process

Abstract: The question addressed in this article is this: How do people make judgments of learning? Judgments of learning (JOLs) are assessments that people make about how well they have learned particular information-that is, predictions about how likely they will be to remember a target item when later given a cue. These assessments are then, presumably, used to control further study (Benjamin, Bjork, & Schwartz, 1998;Dunlosky & Hertzog, 1998;Mazzoni, Cornoldi, & Marchitelli, 1990;Metcalfe, 2002;Metcalfe & Kornell, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 68 publications
7
94
4
Order By: Relevance
“…First, item-by-item JOLs might induce deeper, semantic encoding for all the items, overshadowing the typical effect of generation on memory (Matvey et al, 2001). Second, item-byitem JOLs might divert attention away from the items themselves toward the ratings and cause disruptions in the processing of the words themselves (Son & Metcalfe, 2005). Regardless of the correct explanation, the same empirical result is expected with the perceptual interference manipulation in the present experiment.…”
Section: Methodssupporting
confidence: 45%
“…First, item-by-item JOLs might induce deeper, semantic encoding for all the items, overshadowing the typical effect of generation on memory (Matvey et al, 2001). Second, item-byitem JOLs might divert attention away from the items themselves toward the ratings and cause disruptions in the processing of the words themselves (Son & Metcalfe, 2005). Regardless of the correct explanation, the same empirical result is expected with the perceptual interference manipulation in the present experiment.…”
Section: Methodssupporting
confidence: 45%
“…Indeed, making an SOJ might be similar to the second stage of the two-stage process discussed for delayed judgments of learning (cf. Son & Metcalfe, 2005; see also the two-process hypotheses discussed by Dunlosky et al, 2005). Our results indicate that low-performing students are not completely unaware, which should encourage researchers and practitioners to support students in providing accurate judgments.…”
Section: Discussionmentioning
confidence: 81%
“…A major underlying assumption of metacognition research is that humans are able to monitor their own cognitive processes (Koriat 2002). Systematic examination of several metacognitive memory judgments, such as judgments of learning and feeling of knowing, has demonstrated that there is a high correlation between these judgments and subsequent performance on a recall task, suggesting that individuals can accurately evaluate what they know (Schwartz and Metcalfe 1994;Son and Metcalfe 2005). Recently, Metcalfe and Greene (2007) demonstrated that metacognition of agency, the ability to make judgments about one's own level of physical control, can be systematically evaluated under controlled laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%